Treatment of the Guillain-Barré syndrome by plasma exchange. - Kennard, C (1982)
Twelve consecutive patients with Guillain-Barré syndrome were treated with plasma exchange. Examination two weeks after treatment was commenced showed that three had not improved. Five showed only a minimal improvement, which was considered to be compatible with the natural history of the disease. The remaining four patients showed a more substantial improvement which could have been related to the plasma exchange.